Réponses

Meilleure réponse !
2013-12-01T16:09:37+01:00
A = (x-7)(x+3)+(x+6)(2x-3)
   = x²+3x-7x-21+2x²-3x+12x-18
   =3x²+5x-39
B = (2x+5)²+(3x+7)
   =4x²+20x+25+3x+7
   =4x²+23x+32
C = (6-9w)²
   =36-108w+81w²
D = 2ab+b²
   =b(2a+b)
E = 5x+10
   =5(x+2)
F = (y+2/5)(y-2/5)
   =y²-2/5y+2/5y-4/25
   =y²-4/25
2013-12-01T16:16:55+01:00
A= (x² +3x -7x -21)+ ( 2x² -3x +12x -18)
  = -1x² +5x -39

B= 6x² +14x +15x +35
  = 6x² +29x +35

C= 36 -54w -54w +81w²
  = 36 - 108 +81w²

D= 2ab³

E= 5x +10

F= y² -2/5y + 2/5y - 4/25
  = y² -4/25